The European financial crisis : debt, growth, and economic policy - Godby, Robert. (2014 digital library., 2014)
The European debt crisis has posed a challenge for many people to understand, both non-Europeans and Europeans alike. Even economists, finance specialists, and market commentators are often uncertain of its causes or in the interpretation of events ongoing, or of past events that have taken place that then shaped the current situation. Typically, this lack of comprehension results from a lack of understanding of how European institutions work, the structure of European politics and the Eurozone, the economics of the financial system, or the relationship of debt markets to current government policies in the European Union (EU). The purpose of this book is to describe the causes and outcomes of the European debt crisis (to the date of publication) within the context of three questions most often asked about the debt crisis: (i) what happened, (ii) why did it happen, and (iii) why has the crisis been so difficult for policy makers to address?